The Background Of Calvin’s Thoughts - Philip Suciadi Chia; Juanda Juanda (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2021)
Every age, God will raise up certain people who will become church leaders in their day, to be witnesses of God through the truth of God's word. Their presence did not only appear suddenly, but also through a long process of life and education. In this article, we will explore about The Background of Calvin’s Thoughts, whose influence has revealed the world of theology to this day. Calvin was not only influenced by France Humanism but also medieval Theology at that time. Voluntarism was a popular theology in Calvin era. Calvin received only education in theology from medieval tradition on the first stage of his studies because he never studied theology at university. Calvin’s method which was used to build his theology is inseparable from his studying in Civil Law in Orleans. His studying in Orleans has changed Calvin to be a good jurist and he used his skill later in Geneva to compile codifications of legislation and regulation for Church and government in Geneva. In addition to regulation of life, Calvin also noticed the purity of Christian faith teaching.